Application of total quality management in Leather Industry Development Institute. (30th September 2020) - Hebo, Abduletif H.; Sileyew, Kassu J.; Azene, Daniel K.
The issues related to quality have received more attention in all sectors since years back. Improvement tools, like total quality management, have become prevalent terms in the discussion around quality issues. The intention of this paper is to study total quality management (TQM) implementation in Leather Industry Development Institute (LIDI), and more specifically, to see if the integration of TQM with other tools and techniques could significantly improve the service level of the institute and the satisfaction of the customers. The paper specifically highlighted that the role of senior managers in TQM implementation were minimal due lack of TQM awareness and system integration. To improve this, a phase-based TQM framework has been developed and interpreted comprehensively including implementation strategies, possible improvements and integrations. Due to this, the institute was expected to be passionate with regard to TQM and continuous improvement.